2016
DOI: 10.1007/s00213-016-4239-4
|View full text |Cite
|
Sign up to set email alerts
|

Increased presynaptic regulation of dopamine neurotransmission in the nucleus accumbens core following chronic ethanol self-administration in female macaques

Abstract: Rationale Hypofunction of striatal dopamine neurotransmission, or hypodopaminergia, is a consequence of excessive ethanol use, and is hypothesized to be a critical component of alcoholism, driving alcohol intake in an attempt to restore dopamine levels; however, the neurochemical mechanisms involved in these dopaminergic deficiencies are unknown. Objective Here we examined the specific dopaminergic adaptations that produce hypodopaminergia and contribute to alcohol use disorders using direct, sub-second meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
40
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 47 publications
2
40
1
Order By: Relevance
“…Increased uptake rates have been reported in the NAc of mice (Rose et al 2016), rats (Budygin et al 2007) and monkeys (Siciliano et al 2016) following chronic ethanol exposure, and these findings are supported by increased DAT protein tissue expression (Healey et al 2008). Here we add to the consensus by showing increased uptake rates in the NAc core following a CIE vapor exposure paradigm.…”
Section: Discussionmentioning
confidence: 87%
“…Increased uptake rates have been reported in the NAc of mice (Rose et al 2016), rats (Budygin et al 2007) and monkeys (Siciliano et al 2016) following chronic ethanol exposure, and these findings are supported by increased DAT protein tissue expression (Healey et al 2008). Here we add to the consensus by showing increased uptake rates in the NAc core following a CIE vapor exposure paradigm.…”
Section: Discussionmentioning
confidence: 87%
“…While numerous studies have shown that KORs are G i/o coupled [reviewed by (Bruchas and Chavkin, 2010)], which ultimately reduces neuronal excitability and/or neurotransmitter release in various brain structures (Chen et al, 2015; Crowley et al, 2016; Gilpin et al, 2014; Kang-Park et al, 2013; Karkhanis et al, 2016; Lemos et al, 2012; Li et al, 2012; Rose et al, 2015; Siciliano et al, 2016), studies have also shown that KORs can couple to G s in various cellular models (Baraban et al, 1995; Hampson et al, 2000; Shen and Crain, 1990a, b, 1994) which can increase action potential duration (Shen and Crain, 1990a, b, 1994) and neuronal excitability in dentate granule cells (McDermott and Schrader, 2011). While we have not yet directly investigated these coupling mechanisms, our findings could be explained by a KOR-dependent increase in action potential duration of local GABAergic interneurons, resulting in the observed increase in sIPSC frequency.…”
Section: Discussionmentioning
confidence: 99%
“…Alterations in kappa opioid receptor (KOR) expression and function associated with changes in emotional states have been found in many brain regions implicated in anxiety and reward, including the central amygdala (CeA) (Kissler et al, 2014; Kissler and Walker, 2016), the nucleus accumbens (Karkhanis et al, 2016; Rose et al, 2015; Siciliano et al, 2016), and the bed nucleus of the stria terminalis (BNST) (Crowley et al, 2016). However, the role of KORs in the BLA is not well understood despite it being a brain structure with high levels of KOR expression (Gackenheimer et al, 2005; Slowe et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Given that C57 mice show greater autoreceptor sensitivity in the ventral striatum, a trait that is associated with ethanol use (Siciliano, Calipari, Yorgason, Lovinger, et al, 2016), we next sought to determine the effects of a history of ethanol exposure on dopamine synthesis and autoreceptor sensitivity in C57 mice. Following exposure to one cycle of ethanol (4 days of 16 h ethanol vapor/8 h of withdrawal followed by 3 days of withdrawal), we found that there was no change in dopamine synthesis in the ventral striatum (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Previous work from our lab and others has highlighted changes in dopamine release as well as the ability of presynaptic dopamine D2-type autoreceptors to regulate dopamine release as neuroadaptations induced by chronic ethanol exposure, and important factors in the development of excessive drinking behaviors (Dutton, Chen, You, Brodie, & Lasek, 2016; Karkhanis, Rose, Huggins, Konstantopoulos, & Jones, 2015; Narita, Soma, Tamaki, Narita, & Suzuki, 2002; Rossetti, Melis, Carboni, Diana, & Gessa, 1992; Siciliano, Calipri, Yorgason, Mateo, et al, 2016). One possible explanation for altered dopamine release following ethanol exposure is that ethanol dysregulates the dopamine synthesis process.…”
Section: Introductionmentioning
confidence: 99%